Analysis of Administrative Burden on Semarang Regency Manpower and Transmigration Office - Hasanah, Aprilia Wahidatul; Anggita Oktaviana (Arkus, 2024)
The government organization responsible for managing, promoting, and supervising the employment sector is the Manpower and Transmigration Office or Disnakertrans. The Manpower and Transmigration Department, which is responsible to the Governor through the SEKDA, is tasked with implementing government policies related to employment and transmigration. This research uses a normative juridical method, namely a method that looks at legal doctrine, principles, norms, and general rules through the lens of literature study and legal research, as well as using interviews and observations. This research discusses the administrative burden borne by the community as well as the effectiveness of work programs offered by the Manpower and Transmigration Office. The programs of the Semarang Regency Manpower and Transmigration Office have been running effectively, although there are still several challenges and obstacles. Apart from that, there is an administrative burden on society, where people with low backgrounds have difficulty accessing social media to search for information related to the Manpower and Transmigration Department.